Public Housing Waqf: An Innovative Approach to Sustainable Urban Welfare through Islamic Social Finance - Arizqiya Nurfattah; Fadhila Tianti Mudi Awalia; Azzam Al Hanif; Ibnu Hammam (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Home is one of the primary human needs that supports family education and fosters children's character, preparing the younger generation and society. Unfortunately, not everyone can have the ideal home to create an economically viable family living environment. One of the Islamic financial instruments is waqf, which is expected to support all aspects of finance, including the procurement of houses, both as residences and businesses. The term housing waqf refers to providing services to small communities without housing, which a waqf organization will manage. The purpose of the study is to analyze the impact of the public housing waqf program on people's welfare. This research uses a combination of library and field research to provide both theoretical grounding and empirical evidence. The results show that not everyone can afford a livable house, so the ideal function of the home cannot be realized in family development. This is due to the government's lack of attention to the poor. Waqf for people's welfare emerges as a way to overcome family economic problems and ensure sustainable community welfare.